Pemanfaatan Tanaman Obat Keluarga (TOGA) Sebagai Upaya Mandiri Pencegahan Penyakit - Yestiani Norita Joni; Meilisa Carlen Mainassy; Hardianti Hardianti; Fitriah Suryani Jamin; Halbina Famung Halmar; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Family Medicinal Plants (TOGA) are plants with medicinal properties and are cultivated in home gardens as a form of community self-reliance in maintaining health and preventing disease. The lack of public knowledge regarding the types of TOGA, their processing methods, and their uses is a key reason for implementing this community service program. This activity aims to increase community knowledge and skills regarding the use of TOGA as a preventative measure against various common diseases. The program was implemented among 45 families in Suka Jaya Village through outreach, demonstrations, TOGA planting practices, and mentoring in the preparation of simple herbal concoctions. Evaluation was conducted using pre- and post-tests, practical observations, and interviews. The results of the activity showed a significant increase in community knowledge, from an average score of 52.6 to 88.4 after the education. Eighty-five percent of participants were able to practice TOGA planting, and 78% made simple concoctions such as warm ginger, tamarind turmeric, and lemongrass tea. The community considered the program very beneficial and wanted similar activities to continue regularly. This program can increase community awareness and self-reliance in maintaining health. The use of traditional medicinal plants (TOGA) is considered effective as a disease prevention measure and supports a healthy, natural, and affordable lifestyle. This initiative is recommended for implementation in other regions and further development through further training.